Complications of COVID-19 Vaccines during Pregnancy; a Systematic Review - SeyedAlinaghi, SeyedAhmad; MohsseniPour, Mehrzad; Saeidi, Solmaz; Habibi, Pedram; Dashti, Mohsen; Nazarian, Newsha; Noori, Tayebeh; Pashaei, Zahra; Bagheri, AmirBehzad; Ghasemzadeh, Afsaneh; et al. (Archives of Academic Emergency Medicine, 2022)
Introduction: Rare serious complications have been documented after COVID-19 vaccination as clinical research proceeded and new target populations, such as children and ‎pregnant women, were included. In this study, we attempted to review the literature relevant to ‎pregnancy complications and maternal outcomes of COVID-19 immunization in pregnant women. ‎ Methods: We searched the databases of PubMed, Scopus, Cochrane, and Web of Science on 31 August 2022. The records were downloaded and underwent a two-step screening; 1) title/abstract and then 2) full-text screening to identify the eligible studies. We included English original studies that evaluated the adverse effects of COVID-19 vaccines during pregnancy. Information such as the type of ‎study, geographical location, type of vaccine injected, gestational age, maternal underlying diseases, and ‎complications following the vaccination were extracted into pre-designed tables. Results: According to the findings of included studies, in most of them vaccination had a positive impact and no negative effects were observed. Also, no medical history was reported in 11 articles, and pregnant women had no underlying diseases. Some serious adverse events were reported after ‎vaccination, including miscarriage, paresthesia, uterine contraction, vaginal bleeding, preterm birth, major ‎congenital anomalies, intrauterine growth restriction, and seizure. ‎ Conclusion: Because of limited data availability and the cross-sectional design of most studies, we could neither infer ‎causation between vaccines and incidence of adverse effects nor comment with certainty about any ‎possible adverse outcome of COVID-19 vaccines in vaccinated pregnant women. Consequently, more longitudinal and experimental studies are needed to define the exact adverse effects of COVID-19 vaccines in pregnant women.